What Else Is Needed in the Korean Government's Master Plan for People With Developmental Disabilities? - Jin Yong Lee; Jieun Yun (Korean Society for Preventive Medicine, 2019)
On September 12, 2018, President Jae-In Moon announced the Comprehensive Plan for Lifelong Care for People with Developmental Disabilities, with representatives from the associated government branches (Ministry of Health and Welfare, Ministry of Education, and Ministry of Employment and Labor) in attendance. The goals of this plan are to provide health, medical, rehabilitative, special education, and social welfare services according to the life-stages of the affected individuals; to reduce parental pressure; to promote social interventions; and to enhance community-level participation in order to create a 'welfare society in harmony.' However, in order for the plan to succeed, additional efforts must be made in the following areas. First, an epidemiological survey is needed to understand the scale, prevalence, and incidence of developmental disabilities and to establish an evidence base to support policy development. Second, accurate definitions of developmental disabilities must be established in order to avoid policy discrimination based on impairment type and age. Third, personal evaluations to assess disabled individuals' unmet needs and customized service designs to deliver those needs are required. Fourth, the plan must fulfill the goals of accessibility and fairness that the government intends to provide. Fifth, the government should consider an integrated financial support system and to propose a detailed plan for monetary distributions. Finally, an integrated system that links health, medical, employment, educational, and welfare services must be constructed.